2008
DOI: 10.1111/j.1365-2702.2008.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of and opinions about using standardised care plans in electronic health records – a questionnaire study

Abstract: Use of standardised care plans can improve nursing documentation and facilitate work for nurses. Moreover, it can support nurses in their use of evidence-based nursing methods. The present study shows that nurses have positive attitudes, which could facilitate continued use of standardised care plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 18 publications
5
45
0
1
Order By: Relevance
“…Association uses the definition "care pathways are a methodology for the mutual decision making and organization of care for a well-defined group of patients during a well-defined period" 2 and previous studies found that the benefits of a critical pathway are several 3,5,[7][8][9][10][11][12][13][14] an accepted definition of critical pathway does not exist in Sweden, and no recommendations have been drawn up to address how pathways should be developed. However, critical pathway as a tool has gained recognition in Sweden in recent years.…”
Section: Although Several Definitions Of Critical Pathway Exist For mentioning
confidence: 99%
“…Association uses the definition "care pathways are a methodology for the mutual decision making and organization of care for a well-defined group of patients during a well-defined period" 2 and previous studies found that the benefits of a critical pathway are several 3,5,[7][8][9][10][11][12][13][14] an accepted definition of critical pathway does not exist in Sweden, and no recommendations have been drawn up to address how pathways should be developed. However, critical pathway as a tool has gained recognition in Sweden in recent years.…”
Section: Although Several Definitions Of Critical Pathway Exist For mentioning
confidence: 99%
“…In accordance with other studies (Barker et al 1999;Currie and Harvey, 2000;Furåker et al 2004;Sinuff et al 2007), the nurses conceived of the CP as a source of knowledge in caring. A CP implies that a care plan is visualized, which promotes continuity (Barker et al 1999;Currie and Harvey, 2000;Dahm and Wadensten, 2008) and benefits patients in the form of more security (Furåker et al 2004). The nurses regarded the CP as a planning tool that helped them organize and ensure uniform high standards of caring, rather than leaving the patient to the individual nurse's competence as would otherwise be the case.…”
Section: Quality Of Carementioning
confidence: 99%
“…Some of the nurses viewed the CP as a cross-professional tool that they used together with the nurses-aid and the physician. Other nurses perceived of the CP as a "nurse thing" and suggested that it would be beneficial to caring if the other professional groups involved in caring for the patients used it to a greater extent, a conception also found by Dahm and Wadensten (2008). CP can facilitate communication and cooperation between care professionals (Barker et al 1999;Renholm et al 2002).…”
Section: Quality Of Carementioning
confidence: 99%
“…The nursing literature demonstrates wide variation in how nurses perceive and receive the impact that technology has on their practice. [8][9][10] Similarly variable is the description of nursing's adjustment to the ever-increasing amount of technology in the patient care setting. 11,12 Although there is less literature describing how nursing is influencing the technology that is driving massive change in the patient care environment, there is no doubt that technology has been, and remains, a driving force that is dynamically transforming the clinical and professional environment of nursing.…”
mentioning
confidence: 99%